The Role of Sumoylation in the Response to Hypoxia: An Overview - Filippopoulou, Chrysa (Cells, 2020)
Sumoylation is the covalent attachment of the small ubiquitin-related modifier (SUMO) to a vast variety of proteins in order to modulate their function. Sumoylation has emerged as an important modification with a regulatory role in the cellular response to different types of stress including osmotic, hypoxic and oxidative stress. Hypoxia can occur under physiological or pathological conditions, such as ischemia and cancer, as a result of an oxygen imbalance caused by low supply and/or increased consumption. The hypoxia inducible factors (HIFs), and the proteins that regulate their fate, are critical molecular mediators of the response to hypoxia and modulate procedures such as glucose and lipid metabolism, angiogenesis, erythropoiesis and, in the case of cancer, tumor progression and metastasis. Here, we provide an overview of the sumoylation-dependent mechanisms that are activated under hypoxia and the way they influence key players of the hypoxic response pathway. As hypoxia is a hallmark of many diseases, understanding the interrelated connections between the SUMO and the hypoxic signaling pathways can open the way for future molecular therapeutic interventions.